THE ANALYSIS OF CONFLICT FACED BY MAIN CHARACTER IN THE MOVIE VENOM: LET THERE BE CARNAGE - Konda, Yohanes (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2024)
This study has the objective to analyze the conflict which is being faced by the main characters and also analyzing how the conflicts construct the plot of the movie Venom: Let There Be Carnage. The Movie Venom: Let There Be Carnage as the data source would be analyzed by using descriptive qualitative method. In analyzing the data, two theories related to the topic had been taken namely theory of conflict proposed by Kenney (1966) used to analyze the conflict faced by the main characters and theory of plot proposed by Killman (1977) used to analyze how the conflicts constructed the plot. After doing the analysis, there were 12 conflicts found in the movie, which were categorized by each type. There were 2 conflicts categorized as internal conflict and 10 conflicts categorized as external conflict. All the conflicts faced by the main characters in the movie Venom: Let There Be Carnage were also proven construct the plot of the movie. All the conflict played each role according to part of the plot where the conflict happened. The relation among the conflict as brought the plot until it reached the climax and end in the resolution of the movie. Keyword- Conflict, Plot, Character, Movie, Movie Venom: Let There Be Carnage